Social Safety Nets and its role in the protection of widows (Problems and advancement options) A field study in the Social Welfare Department for Women (Journal of the College of Education for Women, 2019)
Current search problem manifested and widows who community harsh to bear hardships and pains، The goals of continuing the sustainability of life and take responsibility, and especially in light of the difficult circumstances in which Iraq is going through, and the displacement of murder and terrorism, which generated huge numbers of widows and orphans Because of the loss of a breadwinner and which became women and children are the most harm to the victim and as a result of wars and armed tendencies So this research is an important and vital topic opens our horizons important for overlapping roles of women widows and their impact on the achievement and status of Iraqi women and that as long as aptly characterized and their ability to endure hardship and bear the burden and responsibility of her family And research goals to recognize the reality of the women widowed heads of households in the light of the circumstances and the problems they face in the field of home and work, and to highlight the importance of social safety net to protect the widows of marginalization and poverty